Use of Charge Transfer Complexation Reactions for the Spectrophotometric Determination of Sumatriptan in Pharmaceuticals. (31st December 2012) - Prashanth, Kudige N.; Kanakapura, Basavaiah; Raghu, Madihalli S.; Vinay, Kanakapura B.
Abstract : Studies were carried out to use the charge-transfer reactions of sumatriptan (SMT), extracted from neutralized sumatriptan succinate (STS), as n-electron donor with the π -acceptor, 2, 3-dichloro-5, 6-dicyano-1, 4-benzoquinone (DDQ) and σ -acceptor, and iodine (I2 ). The formation of the colored complexes was utilized for the development of simple, rapid, and accurate spectrophotometric methods for the determination of SMT in pure form as well as in its tablets. The quantification of colored products was made spectrophotometrically at 585 nm for the CT complex formed between SMT and DDQ (DDQ method) and at 375 nm for the CT complex formed between SMT and I2 (I2 method). Beer's law is obeyed over the concentration ranges of 4.0–56.0 μ g mL −1 and 2.0–28.0 for DDQ and I2, respectively, with correlation coefficients (r ) of 0.9997 and 0.9998. The analytical parameters such as apparent molar absorptivity, Sandell's sensitivities, and limits of detection (LOD) and quantification (LOQ) are also reported for both methods. The described methods were successfully applied to the determination of SMT in tablets. No interference was observed from the common excipients present in tablets. The reaction stoichiometry in both methods was evaluated by Job's method of continuous variations and was found to be 1 : 1 (donor : acceptor).